2014
DOI: 10.5144/0256-4947.2014.134
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ideal cardiovascular health in a community-based cohort of Middle East population

Abstract: BACKGROUND AND OBJECTIVESTo improve cardiovascular (CV) health of American population, the American Heart Association (AHA) developed definitions of ideal, intermediate, and poor CV health based on 7 accessible health metrics. The applicability of this construct and the distribution of its components in the community-based populations in the Middle East region have not been reported.DESIGN AND SETTINGSA prospective population-based cohort study conducted from 1999 to 2011.METHODSWe used data from phase 4 of Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
(32 reference statements)
3
20
0
Order By: Relevance
“…The frequency of occurrence of all seven CVH indicators is low all over the world, and varies from 0.2% to 15%, depending on geographical location, age, gender, ethnic background, and education level [9,[14][15][16][17]. The rate of achieving ICH results (5-7 ideal metrics) in the researched Polish population was higher than in the Iranian population [18], in the adult population of Republic of Serbia, as well as the adult population of Bosnia and Herzegovina [10]. However, their results were lower than the results of those from Brazil [19], the Canadian research conducted by Maclagan et al [20], the research of the population of Peru [17], and samples of the American population [21,22].…”
Section: Discussionmentioning
confidence: 83%
“…The frequency of occurrence of all seven CVH indicators is low all over the world, and varies from 0.2% to 15%, depending on geographical location, age, gender, ethnic background, and education level [9,[14][15][16][17]. The rate of achieving ICH results (5-7 ideal metrics) in the researched Polish population was higher than in the Iranian population [18], in the adult population of Republic of Serbia, as well as the adult population of Bosnia and Herzegovina [10]. However, their results were lower than the results of those from Brazil [19], the Canadian research conducted by Maclagan et al [20], the research of the population of Peru [17], and samples of the American population [21,22].…”
Section: Discussionmentioning
confidence: 83%
“…Aging and population growth, as well as improvements in life expectancy and other health indicators, will have a major influence on the region's health and resources, particularly among low‐ and middle‐income countries, such as Iran . It is worth noting the high prevalence, morbidity and mortality of cardiovascular diseases (CVD) in general and in older populations in Iran and the Middle East …”
Section: Introductionmentioning
confidence: 99%
“…2 It is worth noting the high prevalence, morbidity and mortality of cardiovascular diseases (CVD) in general and in older populations in Iran and the Middle East. [3][4][5][6] Many studies have shown trends in CVD risk factors in general populations in most regions of the world, but there are few studies in older populations. 7 It is therefore difficult to generalize the efficacy of preventive programs to this group.…”
Section: Introductionmentioning
confidence: 99%
“…It has been predicted that by 2030, over 23.3 million people will die annually from CVD [3], most of which will occur in low-and-middle income countries, such as those in Middle East, where rapid changes in lifestyle, ageing populations and transforming environments all contribute to the dramatic pace of the epidemic [4]. It has been shown that CVDs are becoming a major health problem in this region mostly due to the already high and fast increasing prevalence of cardiovascular risk factors [511]. In spite of having higher CVD morbidity and mortality; compared to Western countries, data in regards to the dynamics of CVD from Eastern population is limited [12].…”
Section: Introductionmentioning
confidence: 99%